Recruitment, use, and satisfaction with a web platform supporting families of children with suspected or diagnosed developmental coordination disorder: a randomized feasibility trial. (3rd October 2019) - Camden, Chantal; Couture, Mélanie; Pratte, Gabrielle; Morin, Mélanie; Roberge, Pasquale; Poder, Thomas; Maltais, Désirée B.; Jasmin, Emmanuelle; Hurtubise, Karen; Ducreux, Edwige; Léger, France; Zwicker, Jill; et al.
ABSTRACT: Objectives . To determine the feasibility of recruiting families of children with suspected or diagnosed developmental coordination disorder (sdDCD) and explore their satisfaction with a web-based intervention Design . A feasibility randomized trial was conducted. Participants were the parents of 5–12-year-old children with sdDCD. The intervention group had access to online resources, group and private forums, and videoconferencing with a therapist. Main outcomes were recruitement and retention rates. Satisfaction was documented through a post-intervention survey and interview. Results . The recruitment rate was seven participants per month ( n = 28 participants) and retention rate was 68%. Satisfaction was moderate. No differences in use and satisfaction were observed between groups. Participants formulated recommendations for improving the intervention, including targeting families earlier in the diagnosis process, and pre-scheduling meetings with therapists. Conclusions . This study demonstrated the feasibility of future trials, and highlighted avenues for improvement. Parent involvement during the development of the intervention is discussed at length. Abbreviations: DCD: Developmental Coordination Disorder; sdDCD: suspected or diagnosed Developmental Coordination Disorder; RCT: randomized-controled trial